2016
DOI: 10.1016/j.cgh.2016.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Peristaltic Reserve, Determined by Multiple Rapid Swallows, Is the Most Frequent Esophageal Motility Abnormality in Patients With Systemic Sclerosis

Abstract: We assessed peristaltic reserve using multiple rapid swallows (MRS) during esophageal high-resolution manometry (HRM) of 111 patients with systemic sclerosis (89 female; ages 42–64 years). We performed a retrospective analysis of HRM studies that included MRS in patients with systemic sclerosis, performed at 2 tertiary referral centers, and compared data with those from 18 healthy volunteers (controls). HRM findings were analyzed according to the Chicago Classification to provide an esophageal motility diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 21 publications
3
63
0
1
Order By: Relevance
“…Potential implications of IEM relate to GERD severity, symptom reporting, and decision making prior to antireflux surgery. Ineffective esophageal motility has a higher prevalence in smooth muscle disorders, such as scleroderma, other connective tissue disorders and gastroparesis, but is not more common in diabetes mellitus, or hypothyroidism . Ineffective esophageal motility has also been reported in Parkinson's disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential implications of IEM relate to GERD severity, symptom reporting, and decision making prior to antireflux surgery. Ineffective esophageal motility has a higher prevalence in smooth muscle disorders, such as scleroderma, other connective tissue disorders and gastroparesis, but is not more common in diabetes mellitus, or hypothyroidism . Ineffective esophageal motility has also been reported in Parkinson's disease .…”
Section: Discussionmentioning
confidence: 99%
“…There is limited understanding of the natural history of IEM. The presence of muscle disorders, particularly connective tissue disorders, may imply progression of IEM to higher grades of hypomotility . The presence of contraction reserve may suggest a better prognosis .…”
Section: Managementmentioning
confidence: 99%
“…We calculated augmentation ratio as the DCI following MRS divided by the median of the non‐failed supine swallows (DCI > 100). We judged a normal response after MRS (augmentation) if there was an increase in contraction vigor, with an augmentation ratio ≧ 1 …”
Section: Methodsmentioning
confidence: 99%
“…The esophagus is the most commonly impacted organ (62.6%), and the development of GERD is the main consequence of disease . A recent study using HRM with multiple rapid swallows suggested that impaired peristaltic reserve was most common motility pattern, but not absent contractility or ineffective esophageal motility with or without LES hypotension, which supports myopathy as the primary pathogenesis of esophageal dysfunction associated with SSc . As a consequence of dysmotility, the dilated esophagus plays an important role in the pathogenesis of intestinal lung fibrosis.…”
Section: Aspiration and Gerd In Pulmonary Fibrosismentioning
confidence: 99%